Synthesis of double perovskite LaMgCo2O5.5 nanopowder and its robust electrical humidity sensing behavior. Issue 10 (15th May 2022) - Maurya, Dheeraj Kumar; Chaudhary, Priyanka; Yadav, Bal Chandra; Angaiah, Subramania
Abstract: Perovskites materials are quite popular as a potential alternative for sensing material development. Oxygen deficiency in these species leads to enhanced chemical reactivity and affinity in the ambient environment. Here, we have investigated the electrical humidity sensing behavior of double perovskite LaMgCo2 O5.5 thin film at various frequencies, i.e., 100 Hz, 1 kHz, 100 kHz, and 1 MHz. LaMgCo2 O5.5 (LMCO) nanopowder is successfully synthesized by citric acid assisted combustion method and then it is fabricated as a thin film using the spin coating method. The morphological texture is investigated using SEM analysis, revealing spheres with agglomerated nanoparticles, whereas the compositional analysis of the LMCO is done by EDX elemental analysis. Crystalline nature is confirmed by the XRD pattern exhibiting an average size of ∼22 nm. The optical energy band gap of LMCO thin film is found to be 1.5 eV. Thermal studies are conducted using TG-DTA analysis. A high porous thin film exhibits a sensitivity of 10.22 MΩ/%RH with a rapid response and the recovery time of 21 s and 26 s, respectively, at 100 Hz. This research provides a better humidity sensing pathway for p-type materials with oxygen defect engineering.